Evaluasi Parameter Fisikokimia, Farmakokinetika, dan Farmakodinamika Senyawa Fisetin Dalam Desain Obat - Arif Fadlan; Tri Warsito; Sarmoko Sarmoko (Akta Kimia Indonesia, 2022)
Fisetin is a flavonoid with flavonol framework found in various fruits and vegetables such as strawberries, apples, persimmons, lotus root, grapes, onions, kiwi, peaches, and others. Fisetin with four hydroxyl and one oxo groups shows biological activities such as antioxidant, anti-inflammatory, antimicrobial, antidiabetic, and anticancer. Thus, fisetin becomes an interesting target for finding alternative therapeutic agents. However, more than 50% of drug candidates fail due to poor absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis. This research studied the physicochemical, pharmacokinetic, and pharmacodynamic parameters of fisetin to avoid those problems by using PreADMET, SwissADME, dan Molinspiration. The results revealed good physicochemical parameters for fisetin with potential to be used as oral or transdermal. Fisetin was known to be quite easy synthesized, crossed the BBB, non-toxic, not carcinogenic in mice, and had a medium cardiotoxicity. Furthermore, fisetin inhibited kinases, nuclear receptor ligands, and enzymes. It was moderate as GPCR ligands and ion channel modulators.